Mechanical and Electrical Properties: Electrospun Alginate/Carbon Nanotube Composite Nanofiber - Islam, Md Shahidul; Ashaduzzaman, Md; Masum, Shah Md; Yeum, Jeong Huyn (Dhaka University Journal of Science, 2012)
Nanofibers of the composite of alginate (Alg) and carbon nanotube (CNT) were prepared using electrospinning method out of aqueous solutions. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), mechanical measurement, and electrical conductivity were done to characterize the Alg/CNT composite nanofibers morphology and properties. The SEM and TEM images show the CNT to be well incorporated along the nanofibers. The study shows that the introduction of CNT results in improvement in tensile strength and electrical conductivity of the Alg matrix. The electrospinning of Alg/CNT composites could potentially supply useful options for the fabrication of biomaterial scaffolds. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10350 Dhaka Univ. J. Sci. 60(1): 125-128 2012 (January)